Implementasi Metode Keteladanan dalam Meningkatkan Mutu Pendidikan Akhlak pada Mata Pelajaran PAI: Studi Kasus di SMP Islam An-Nasiriin Jakarta Barat - Sholichah, Aas Siti; Alwi, Wildan; Fajri, Ahmad (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2020)
This study aims to determine the implementation of exemplary methods in improving the quality of moral education in Islamic Education subjects at an-Nasirin Islamic Junior High School, West Jakarta. The method in this research uses qualitative methods with a field study approach. The research technique used is to use data triangulation, namely combining observation, interviews and documentation. The implementation of exemplary methods in improving the quality of moral education in Islamic Education subjects at An-Nasiriin Islamic Middle School, namely through the moral values that have been conveyed by the term Principles of Adab. The term principle of adab is adab-or ethics in daily activities at school, such as speaking honestly, politely, respecting teachers and friends, eating, going well. The mention of the term is intended to remind students of the moral values that have been taught can be embedded and implemented. To strengthen the values of these principles of adab, the teacher implements exemplary method